Gpu-Dem Study of the Flow and Energy Dissipation Behaviors of Burden Materials in a Full Bell-Less Blast Furnace Charging System - Jacobs-Capdeville, P (Elsevier B.V., 2025)
The blast furnace bell-less top charging system involves multiple handling steps that affect burden distribution in the furnace throat. This study employs a GPU-DEM model to analyze particle motion and energy dissipation of burden materials from the belt conveyor to the furnace throat, providing insights into flow behavior, segregation, degradation, and erosion. Particle properties and size distributions strongly affect the flow structure. Pellets exhibit higher velocities than lumps, sinters, and coke, with differences decreasing in the rotating chute. Four regions of high energy dissipation were found, with coke and sinter degradation reaching 15 % of the feed and lump and pellet degradation remaining around 1 %. Wear intensifies with broader particle size distributions, driven by shear energy. Segregation before hopper filling is minimal, but in-hopper segregation significantly impacts in-furnace segregation, where larger particles accumulate at the periphery and top. Heap formation arises mainly from shifts between rolling and impact energy dissipation. © 2024